IDENTIFIKASI FAKTOR PENYEBAB KETERLAMBATAN HANDLING KEMASAN KARTON MELALUI PENDEKATAN DIAGRAM FISHBONE UNTUK PENINGKATAN EFISIENSI OPERASIONAL PT DSV SOLUTIONS INDONESIA SEMARANG SITE - Afifah Khairunisa; Agus Rahman Setiawan (Jurnal Riset Multidisiplin Edukasi, 2026)
Carton packaging without a front opening often creates significant obstacles in warehouse operations, particularly during the item-retrieval process when cartons are stacked. this condition requires operators to lift or disassemble the cartons before accessing the contents, resulting in longer processing times and reduced operational efficiency. this study aims to analyze the root causes of inefficiencies in the retrieval process by applying the fishbone diagram method as a tool to identify contributing factors. the analysis reveals that the issue is influenced by factors related to manpower, work methods, machinery/equipment, materials, and the working environment. based on these findings, a redesigned carton using a front opening box concept was proposed, allowing operators to retrieve items from the front without moving other stacked cartons. this solution not only improves operator ergonomics but also reduces handling time and minimizes the risk of product damage. initial evaluation indicates that the new design significantly enhances speed, safety, and comfort in daily operational activities. this study demonstrates that the fishbone approach is effective for identifying root causes and formulating practical packaging improvement recommendations applicable to warehouse environments.